PRODUÇÃO E IMPLANTAÇÃO DE MUDAS DE CANAFÍSTULA (Peltophorum dubium) E PARA TUDO (Tabebuia aurea) EM ÁREA DEGRADADA DA UEMS, AQUIDAUANA/MS - NOBRE, Cindy Costa; WOICIECHOWSKI, Thiago; FANOLA, Hannah Cristina Botelho Lima (ANAIS DO ENIC, 2017)
-